Extensional flow behaviour of natural fibre-filled dough and its relationship with structure and properties - Sousa, Isabel (2010)
There is an increasing awareness about the role of fibres as multifunctional substances, positively affecting the activity of the human body. From the structural point of view, insoluble fibres are known to have a strong impact on food texture. This work is part of a broader project aimed at understanding the role of fibres from different sources in traditional cookies delectableness. The impact on cookie dough characteristics, when enriched with dietary fibre, was evaluated by dynamic oscillatory tests, transient uniaxial extensional viscosity measurements and texture profile analysis. Three different sources of fibre were added: oat from cereals, orange from fruits and pea from legumes, at contents ranging from 0 to 10 g. In terms of processibility, there were serious difficulties in processing some of these doughs, especially those with fibre addition levels over 8 g for oat and orange and 9–10 g for pea. However, the results for the mechanical spectra of these doughs are similar to that of the standard dough without fibre. Tests in compression with a 4mm cylinder in a 25mm flask filled with dough showed to be more sensitive than oscillatory tests but still the results were somewhat difficult to interpret in terms of describing the differences in the processing behaviour of these doughs. Thus, extensional uniaxial tests were performed (for the first time in this type of materials, i.e., with no developed gluten) and showed to be suitable to describe the modification in dough structure, showing an increase of extensional viscosity for the dough with orange or oat fibre at levels of 4, 8 and 10 g, whereas for the pea fibre dough, no significant changes on the extensional behaviour were observed for formulations with up to 10 g of fibre, which was in general agreement with the processibility studies.